Confirming the efficacy of intravenous immunoglobulin in CIDP through minimum clinically important differences: shifting from statistical significance to clinical relevance. Issue 11 (20th July 2010) - Merkies, I S J; van Nes, S I; Hanna, K; Hughes, R A C; Deng, C
Abstract : Background: The ICE trial demonstrated the efficacy of immune globulin intravenous (IGIV-C) over placebo in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). However, improving the interpretability of the results by analysing the minimum clinically important difference (MCID) had not been considered. Objectives: To identify MCID thresholds of various outcome measures using different methods and to test treatment differences (IGIV-C vs placebo) using these thresholds. Methods: One anchor-based (Short Form-36 question 2) and three distribution-based (½ SD, 1 SE of measurement, and effect size) techniques were employed to identify MCID cut-offs for various impairments (electromyographic parameters, Medical Research Council (MRC) sum score, grip strength, inflammatory neuropathy cause and treatment (INCAT) sensory sum score), disability (INCAT scale score, Rotterdam handicap scale (RHS) score) and quality of life (SF-36). IGIV-C or placebo was administered every 3 weeks for up to 24 weeks to 117 CIDP patients. Patients who did not improve by ≥1 point on the INCAT scale received alternate treatment. The proportion of patients with results exceeding identified MCID thresholds was compared. Results: MCID cut-offs for outcomes were determined using each method. For the INCAT disability scale (primary ICE-trial outcome), all MCID methods identified significantly more responders with IGIV-C than placebo. Significant differences favouring IGIV-C were also demonstrated for various nerve conduction parameters, MRC sum score, grip strength, RHS score and SF-36 physical component summary score. Conclusion: In addition to being statistically significant, all MCID analyses showed that CIDP improvements with IGIV-C are clinically meaningful. Consideration of MCID is recommended in future therapeutic trials. Trial Registration Number: NCT00220740 (http://ClinicalTrials.gov )